2019
DOI: 10.5897/err2019.3830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seventh-grade Turkish and Iranian social studies textbooks in terms of value education

Abstract: One of the objectives of comparative education research is to compare within a certain period of time educational systems that have developed in similar or different environments and processes. The aim of this qualitative study is to compare the value education in Turkish and Iranian seventh-grade social studies textbooks. Data were collected using document analysis. Results show that both books underscore the values of scientificity, sensitivity and responsibility. Unlike the Turkish social studies textbook, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Finally, in 7th-grade, Türkiye used 3 poems, whereas Iran used 1. In the current study, although there are some differences in the results obtained for poems, Kaya (2019) conducted a study that contains similarities by considering all the content in 7th-grade social studies textbooks in Türkiye and Iran. In his study, Kaya (2019) found that in the Türkiye textbook, values such as scientificity, freedom, responsibility, and sensitivity were prioritized respectively, while in the Iran textbook, values such as sensitivity, responsibility, scientificity, and aesthetics were prioritized respectively.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in 7th-grade, Türkiye used 3 poems, whereas Iran used 1. In the current study, although there are some differences in the results obtained for poems, Kaya (2019) conducted a study that contains similarities by considering all the content in 7th-grade social studies textbooks in Türkiye and Iran. In his study, Kaya (2019) found that in the Türkiye textbook, values such as scientificity, freedom, responsibility, and sensitivity were prioritized respectively, while in the Iran textbook, values such as sensitivity, responsibility, scientificity, and aesthetics were prioritized respectively.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…In the current study, although there are some differences in the results obtained for poems, Kaya (2019) conducted a study that contains similarities by considering all the content in 7th-grade social studies textbooks in Türkiye and Iran. In his study, Kaya (2019) found that in the Türkiye textbook, values such as scientificity, freedom, responsibility, and sensitivity were prioritized respectively, while in the Iran textbook, values such as sensitivity, responsibility, scientificity, and aesthetics were prioritized respectively. While this study only focuses on poems, and the aforementioned study (Kaya, 2019) examines the entire content of the textbooks, it can be observed that freedom and responsibility are common values for Türkiye, and responsibility and aesthetics are common values for Iran, even though it does not allow for a direct comparison.…”
Section: Discussion and Resultsmentioning
confidence: 99%